Understanding Chinese society - Zang, Xiaowei (Routledge, 2011)
"As China becomes more powerful--economically, politically, and militarily--and interaction between the Chinese and people outside China becomes more frequent, it becomes more and more important that we understand the social factors which influence the daily lives of China's population. This new introductory text book is suitable for all students taking a course on Chinese society. It presents students with both historical and contemporary contexts and references the latest available scholarship. With chapters covering all key aspects of life in China, including religion, social policy and welfare, the history and impact of the Chinese Communist Party, familial relationships, ethnicity, gender, the media and the education system, it gives the reader a user-friendly and comprehensive introduction to the issues affecting Chinese society today. It also includes handy pedagogical features such as a chronology of the People's Republic of China, further reading suggestions, related novels, films and autobiographies for further study."--Publisher's description.